Quality of Nursing Care in Hospitalized Patients of the Carlos Lanfranco La Hoz Hospital, 2019 - Amancio Izquierdo-Príncipe; Jaqueline Garcia-Núñez; Brian Meneses-Claudio; Hernan Solis-Matta; Lourdes Matta-Zamudio (Advances in Science, Technology and Engineering Systems Journal, 2020)
Background: The quality of care of the nursing professional in relation to the hospitalized patient refers to the set of knowledge and attitudes that the nursing professional must provide quality care, preventing risks and improving patient satisfaction, for which its objective is to determine the quality of nursing care in hospitalized patients at the LanFranco la Hoz Hospital. Method: it is a quantitative, non-experimental, descriptive, and cross-sectional study with a study population of 143 patients in total hospitalized at the Carlos LanFranco la Hoz Hospital. Results: The results obtained in the quality of nursing care in hospitalized patients, it can be seeing that 86 patients representing 60.1%, are moderately satisfied, followed by 36 patients that represent 25.2% are satisfied, 12 patients that represent 8.4% are dissatisfied, 7 patients that represent 4.9% are very satisfied and finally 2 patients that represent 1.4% are very dissatisfied. In the dimension, experience of the nurse in the care of hospitalized patients, it can be observed 69 patients that represents 48.3% are moderately satisfied with the experience of the nurse in the care and in the dimension satisfaction with nursing care in hospitalized patients, it can be see 93 patients that represents 65% are satisfied with the quality of care. Conclusions: It is concluded that the high demand for patients sustains a decrease in quality nursing care due to the scarcity of human resources in the hospital and it is recommended that the hospital have a permanent evaluation system of quality of care to meet the expectations of hospitalized patients.
Keywords: Quality of care; Patient Satisfaction; Hospitalized Patients; Nursing Care; Hospital